2023
DOI: 10.1002/app.54638
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and characterization of (PVDF/PEO)/AgBiSe2 polymeric membrane with enhanced visible light photocatalytic performance

A. M. Ismail,
R. A. Nasr,
Talaat A. Hameed

Abstract: Driven by the visible band gap, silver bismuth selenide (AgBiSe2) was loaded in PVDF/PEO blend to enhance the photodegradation of Maxilon blue dye. AgBiSe2 nanoparticles were successfully synthesized by facile solvothermal approach and then loaded to PVDF/PEO (80/20) by 10, 20, and 30 wt%, by evaporative casting method. The X‐ray results in tandem with the Fourier transform infrared (FTIR) established the successful fabrication of (PVDF/PEO)/x(AgBiSe2) polymer nanocomposites. The X‐ray analysis verified the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 75 publications
(121 reference statements)
0
1
0
Order By: Relevance
“…After irradiation, the absorbance maximum decreased to 1.75, 1.33, 0.99, and 0.93 from 15 minutes to 60 minutes in the UV chamber. The experimental result has shown that the maximum degradation occurred when the solution was placed for 60 minutes in the UV chamber in the presence of the catalyst and Hydrogen peroxide [37] (Figure 13).…”
Section: Measurement Of Absorbance Maximum After Degradationmentioning
confidence: 99%
“…After irradiation, the absorbance maximum decreased to 1.75, 1.33, 0.99, and 0.93 from 15 minutes to 60 minutes in the UV chamber. The experimental result has shown that the maximum degradation occurred when the solution was placed for 60 minutes in the UV chamber in the presence of the catalyst and Hydrogen peroxide [37] (Figure 13).…”
Section: Measurement Of Absorbance Maximum After Degradationmentioning
confidence: 99%